An optimum value of dynamic communication performance for midimew connected mesh network - Yahya Hag, Ala Ahmed; Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Tengku Sembok, Tengku Mohd (Indian Society for Education and Environment & Informatics Publishing Limited, 2016)
A Midimew connected Mesh Network (MMN) is a proposed hierarchical interconnection network in which numerous basic modules are interconnected in a hierarchical fashion to construct a massively parallel computer. Here, the basic module is the first level of the network which is connected by mesh network while higher level network is connected by a midimew network. In this study, we have evaluated a dynamic communication performance of a variety of MMN using the TOPAZ simulator using a deadlock free routing algorithm with uniform traffic patterns, whereby the dimension order routing and virtual cut-through flow control are used. It is found that the saturation throughput of the Virtual MMN (VMMN) is higher than that of Horizontal MMN (HMMN), Symmetric MMN (SMMN), and Tori connected mESH network (TESH).